2016
DOI: 10.3390/molecules21030289
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of the α-Al2O3-PETN Interface

Abstract: Abstract:Optical absorption measurements are combined with electronic structure calculations to explore photochemistry of an α-Al 2 O 3 -PETN interface formed by a nitroester (pentaerythritol tetranitrate, PETN, C 5 H 8 N 4 O 12 ) and a wide band gap aluminum oxide (α-Al 2 O 3 ) substrate. The first principles modeling is used to deconstruct and interpret the α-Al 2 O 3 -PETN absorption spectrum that has distinct peaks attributed to surface F 0 -centers and surface-PETN transitions. We predict the low energy α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Because energetic materials are densely packed, we predict that there are many other manifestations of the crystal arrangement governing the decomposition chemistry and hence the sensitivity. To mention just a few vivid illustrations, we recall the shear-strain effect in DADNE [21,124,141], the aspects of autocatalysis analyzed for DADNE and TATB [124], polarization-induced charge transfer in δ-HMX [96], enhanced optical absorption on PETN-MgO interfaces [142], and photocatalytic dissociation of PETN molecules adsorbed on F 0 -centers on the α-Al 2 O 3 (0001) surfaces [143]. A variety of structural and electronic defects also play a role in changing decomposition chemistry in organic molecular crystals [19,122,133,144,145,146].…”
Section: Discussionmentioning
confidence: 99%
“…Because energetic materials are densely packed, we predict that there are many other manifestations of the crystal arrangement governing the decomposition chemistry and hence the sensitivity. To mention just a few vivid illustrations, we recall the shear-strain effect in DADNE [21,124,141], the aspects of autocatalysis analyzed for DADNE and TATB [124], polarization-induced charge transfer in δ-HMX [96], enhanced optical absorption on PETN-MgO interfaces [142], and photocatalytic dissociation of PETN molecules adsorbed on F 0 -centers on the α-Al 2 O 3 (0001) surfaces [143]. A variety of structural and electronic defects also play a role in changing decomposition chemistry in organic molecular crystals [19,122,133,144,145,146].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, work on 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) did not consider cyclization as the primary method of initiation due to high activation barriers. [36] Although many factors unique to the solid state can influence the sensitivity of energetic materials, [1][2][3]27] gas-phase calculations can contribute to understanding how intramolecular interactions influence sensitivity. Theoretical measures of bond strength include the Atoms-In-Molecules (AIM) method, [37,38] unimolecular decomposition activation barriers, [22,23] bond dissociation energies (BDEs) [39] and Mulliken population analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum-chemical calculations lifted the contradiction and suggested that PETN–MgO interfaces, formed in the mixture, absorb light with the low energy of 1.3 eV due to oxygen vacancy-adsorbent interactions and electronic states generated in the band gap. , This absorption triggers the decomposition chemistry of PETN with a much lower activation barrier than the conventional thermal initiation . The similar situation was observed in the alumina-PETN mixtures . It was established that the interaction of energetics with defects leads to a formation of charged or excited radicals that govern photodecomposition.…”
Section: Introductionmentioning
confidence: 84%
“…50 The similar situation was observed in the alumina-PETN mixtures. 53 It was established that the interaction of energetics with defects leads to a formation of charged or excited radicals that govern photodecomposition. These developments provoked a set of outstanding questions, such as whether a photocatalytic additive can be deliberately chosen (for instance, as a dopant) to facilitate conventional decomposition reactions or initiate an unusual photodecomposition pathway in energetic materials.…”
Section: Introductionmentioning
confidence: 99%